The Effectiveness Of E-Counseling toward Weight Loss Program Among Obesity Students - Siregar, Fitri Nur Malini; Utami, Ratih Yulistika (ANATOMICA MEDICAL JOURNAL | AMJ, 2024)
A pandemic of obesity has caused many people to gain weight during the COVID pandemic.This pandemic has also caused people to minimize seeking treatment at health facilities. Therefore, the e-counseling method in the weight loss program is considered capable of being a treatment for obesity during a pandemic. This study aims to determine the effectiveness of e-counseling on the weight loss management program among obesity students. Methods: This study is a retrospective cohort analytic study involving obese patients. Sixty subjects was taken by the consecutive sampling method. The E-counseling method that the patient undergoes is in the form of face-to-face virtual counseling at the beginning of the program about 15 minutes per person, then a meal plan is given by reducing 500-700 kcal from the daily intake. This is followed by providing education on healthy lifestyles and periodic consultations through the WhatsApp group while undergoing the weight loss program. Results:. After undergoing the intervention for 1 month, the effects of losing as much weight as 3,39 – 4,21 kg (p0.001) used T- dependent test. Body mass index of research subjects also decreased as much as 1,72 kg/m2 to 1,88  kg/m2 (p0.001) used T dependent test. Waist circumference measurements also showed a decrease as much as  4,4 cm to 5,8 cm (p0.001) used Wilcoxon test. Conclusion: The weight loss program through the e-counseling method was clinically and statistically proven effective in reducing body weight, body mass index and waist circumference in research subjects after 1 month of intervention.Keywords: e-counseling, obesity, body mass index, waist circumference